Chinese Confucianism, Japanese Practice - Zhou, Jinghao (New Dynamics in Asia, 2020)
The culture of a nation is the DNA of the nation and significantly influences the direction of the nation’s development and its foreign policy. China is the birth country of Confucianism; and Confucianism has been the mainstream of Chinese traditional culture for over 2,000 years. Japanese civilization has a Chinese origin, including Confucianism and the civil service examination system. Since Confucianism was introduced into Japan in the fourth century, it has gradually become an integrated part of Japanese culture. To improve China–Japan relations, it is necessary to consider the similarities and differences of practicing Confucianism in the two countries. This paper attempts to take on this task by emphasizing how Japan has Japanized Confucianism while the Chinese Communist Party (CCP) has used Confucianism to justify its legitimacy. This paper will argue that Japan does not simply copy Chinese Confucianism, but has selectively practiced Confucianism and used it for its own national agenda.